Effect of Post Heated TiN Coating on Pitting Corrosion of Austenitic Stainless Steel - Hsu, Cheng-Hsun; Liu, Hong-Tsair; Huang, Wei-Che; Lin, Meng-Ru (Journal of Coating Science and Technology, 2016)
This study used cathodic arc deposition technique to coat TiN film on 316L austenitic stainless steel, and then the coated specimens were heat-treated at the different temperatures. Observation of coating morphology and corrosion tests were conducted for exploring the effect of post-heating temperature on composition, microstructure, and corrosion behavior of the coatings. The results showed when the heating temperature was up to the range of 500-600 oC, a Ti-N-O mixed film consisting of the two TiO2 and TiN phases was formed on the outer layer. Particular, the film heated at 500 oC had a dense structure as well as homogeneous chemical composition. Such the result could effectively inhibit pitting corrosion of 316L stainless steel in 3.5 wt% NaCl and 10 vol% HCl solutions.